Insight into the intrinsic mechanism of improving electrochemical performance via constructing the preferred crystal orientation in lithium cobalt dioxide - Yubiao Niu (Chemical Engineering Journal, 2020)
Surface properties of cathode materials play important roles in the transport of lithium-ions/electrons and the formation of surface passivation layer. Optimizing the exposed crystal facets of cathode materials can promote the diffusion of lithium-ions and enhance cathode surface stability, which may ultimately dominate cathode’s performance and stability in lithium-ion batteries. Here, polycrystalline LiCoO2 (LCO) thin films with (0003) and {101} preferred orientations were prepared as the well-defined model electrodes. In situ Current-Sensing Atomic Force Microscopy (CSAFM) was employed to investigate the lithium de-intercalation and electronic conductivity evolution of the (0003) and {101} facts in organic electrolyte at the nanoscale. It was found that the lithium deintercalation following a “Li-rich core model” in the LCO grains, and the LCO grains with (0003) crystal face show less conductivity than those with {101} faces. Moreover, X-ray Photoelectron Spectroscopy characterization of the charged electrode surface indicates that a denser surface passivation layer is formed on {101} than that on (0003) crystal faces. This is caused by the lower adsorption energy of decomposition molecule on {101} crystal faces and higher work function (due to the surface atomic structure) for {101} crystal faces, as confirmed by Density Functional Theory (DFT) and Kelvin probe force microscopy (KPFM) results. In addition, electrochemical measurements confirm that the thin film electrodes with {101} preferred orientation not only show smaller electrode polarization, but also more readily form a stable surface passivation layer compared with the (0003) preferred orientation. This work highlights the importance of cathode conductivity, and suggests that the LCO {101} facet atomic structure may thermodynamically promote the physical/chemical adsorption and decomposition of electrolyte.